Difficulties in preparing a school project in the school planning process (Journal of Parents and Teachers, 2014)
The process of educational reform that has taken place during the last decades has entailed a change that affects the vision of the school as an organization. Every school must present a Center Educational Project that answers questions about its principles, identity, goals, systems, structures and, ultimately, organization. The aforementioned document is not always easy to elaborate, so this article presents a list of the most frequent errors of a Center Educational Project, and its uses.
Keywords: educational center project; organization.